The utilization of different combination and level of corn, tapioca and pollard on the growth performance of black tiger shrimp (Penaeus monodon) juvenile - M. Agus Suprayudi; Dedi Yaniharto; . Ridwan (Jurnal Akuakultur Indonesia)
This experiment was conducted to evaluate the effect of carbohydrate level and sources on the growth performance of black tiger shrimp Penaeus monodon juvenile. Four shrimp diet contains isoprotein (35%) and isoenergy-protein ratio (8.2 kkcal/g protein) but different in carbohydrate level were used in this experiment. Diet A and B containing carbohydrate at the level of 34%, while diet C and D contain 40% of carbohydrate.  Diet A and diet C have similar carbohydrate source pollard and corn plus tapioca at the ratio of 1:1, where diet B and D was 2:1:1.  Shrimp with 1.5±0.1 g of average body weight were reared in aquarium at the density of 10 shrimp/aquaria and fed 4 times daily at the level of 8% of body weight. Feed consumption, total and protein digestibility, protein and lipid retention, relative growth rate, feed efficiency, survival rate and feed conversion ratio was used as evaluating parameters. The results showed that all diets  have similar  effect on total and protein digestibility, protein and lipid retention, relative growth rate, feed efficiency, and survival rate (P>0.05). It is concluded that Penaeus monodon juvenile could utilize carbohydrate until the level of 40%, and shrimp could utilize corn and tapioca as good as pollard. Keyword: Peneaus monodon, carbohydrate, pollard, corn, tapioca, growth ABSTRAK